2020
DOI: 10.1253/circrep.cr-19-0117
|View full text |Cite|
|
Sign up to set email alerts
|

Cardioprotective Effects of Rivaroxaban on Cardiac Remodeling After Experimental Myocardial Infarction in Mice

Abstract: It has been reported that combination therapies that include low-dose rivaroxaban seem to be effective in secondary prevention of acute coronary syndrome, 11 which suggests that rivaroxaban is effective not only for atrial fibrillation and venous thrombosis but also for coronary artery thrombosis. However, there is insufficient evidence about the cardioprotective effects of rivaroxaban on cardiac remodeling after MI. Rivaroxaban also exhibits anti-inflammatory properties, acting through amelioration of proteas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…If commenced immediately after surgery or up to 24 hours thereafter, rivaroxaban applied in chow prevents intravascular thrombosis, improved cardiac systolic function, and decreased IS and inflammatory markers to variable extents. Within the infarct zone, levels of TNF α , tissue growth factor β , and both protease-activated receptors 1 and 2 are reportedly suppressed, while noninfarcted areas exhibit lower levels of atrial natriuretic peptide and NH 2 -terminal pro-B-type natriuretic peptide, activated ERK, and cardiomyocyte hypertrophy ( Bode et al, 2018 ; Nakanishi et al, 2020 ). Rivaroxaban also improved cardiac function and survival and suppressed transcription of IL-6 and collagens in a mouse model of secondary IRI prevention.…”
Section: Effects Of Pharmacological Treatment Of Comorbidities On Car...mentioning
confidence: 99%
“…If commenced immediately after surgery or up to 24 hours thereafter, rivaroxaban applied in chow prevents intravascular thrombosis, improved cardiac systolic function, and decreased IS and inflammatory markers to variable extents. Within the infarct zone, levels of TNF α , tissue growth factor β , and both protease-activated receptors 1 and 2 are reportedly suppressed, while noninfarcted areas exhibit lower levels of atrial natriuretic peptide and NH 2 -terminal pro-B-type natriuretic peptide, activated ERK, and cardiomyocyte hypertrophy ( Bode et al, 2018 ; Nakanishi et al, 2020 ). Rivaroxaban also improved cardiac function and survival and suppressed transcription of IL-6 and collagens in a mouse model of secondary IRI prevention.…”
Section: Effects Of Pharmacological Treatment Of Comorbidities On Car...mentioning
confidence: 99%
“…RIV has shown protective effects in a variety of mouse models. The study conducted by Nakanishi et al (2020) found that RIV protected against cardiac dysfunction by inhibiting PAR-1, PAR-2 and proinflammatory cytokines, with effects observed after seven days in MI model mice. Another study conducted by Bode et al (2018) showed that RIV did not reduce cardiac dysfunction in PAR-2 −/− mice.…”
Section: Introductionmentioning
confidence: 98%
“…Daci et al showed that pretreatment with rivaroxaban attenuated lipopolysaccharide (LPS)-induced acute vascular inflammation and contractile dysfunction in LPS-injected rats [ 41 ]. Nakanishi et al demonstrated that rivaroxaban protected against cardiac dysfunction after myocardial infarction in mice [ 42 ]. Reductions in protease-activated receptor (PAR)-1, PAR-2, and proinflammatory cytokines in the infarcted area were associated with the cardioprotective effects of rivaroxaban.…”
Section: Introductionmentioning
confidence: 99%